El Ms. 270 de la Biblioteca Nacional de Madrid, ¿un misal aragonés del siglo XII-XIII? - Ruiz Torres, Santiago (Miscel·lània litúrgica catalana, 2014)
The ms. 270 of the Biblioteca Nacional de Madrid is one of the most ancient missals of its collection. Despite of the limited number of formularies, it contains some elements interesting for a liturgical analysis. This article, on the grounds of the most ancient part of the manuscript (f. 1-37), tries to place this liturgical source in the ecclesiastical peninsular frame and, as far as possible, determine its probably aragonese origin. For this purpose its affinity with different sacramentaries, particularly from the Pyrenaic area, is studied. The importance of its musical repertory is also considered from a paleographical and melodical perspective.